2016
DOI: 10.1038/srep21653
|View full text |Cite
|
Sign up to set email alerts
|

A pilot-scale forward osmosis membrane system for concentrating low-strength municipal wastewater: performance and implications

Abstract: Recovery of nutrients and energy from municipal wastewater has attracted much attention in recent years; however, its efficiency is significantly limited by the low-strength properties of municipal wastewater. Herein, we report a pilot-scale forward osmosis (FO) system using a spiral-wound membrane module to concentrate real municipal wastewater. Under active layer facing feed solution mode, the critical concentration factor (CCF) of this FO system was determined to be 8 with 0.5 M NaCl as draw solution. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 47 publications
3
56
0
Order By: Relevance
“…Concentrating the FS reduces the footprint and improves the resource recovery of the downstream treatment processes such as anaerobic digestion (Chen et al, ; Linares et al, ; Xie, Nghiem, Price, & Elimelech, ). A pilot‐scale FO trial has proven that FO is feasible to concentrate low‐strength municipal wastewater in full‐scale applications (Wang, Zheng, Tang, Wang, & Wu, ). Furthermore, thin‐film composite (TFC) FO membranes achieve initial water flux of 18 L m −2 hr −1 or higher (Kwan et al, ; Lutchmiah, Verliefde, Roest, Rietveld, & Cornelissen, ; Yip, Tiraferri, Phillip, Schiffman, & Elimelech, ).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrating the FS reduces the footprint and improves the resource recovery of the downstream treatment processes such as anaerobic digestion (Chen et al, ; Linares et al, ; Xie, Nghiem, Price, & Elimelech, ). A pilot‐scale FO trial has proven that FO is feasible to concentrate low‐strength municipal wastewater in full‐scale applications (Wang, Zheng, Tang, Wang, & Wu, ). Furthermore, thin‐film composite (TFC) FO membranes achieve initial water flux of 18 L m −2 hr −1 or higher (Kwan et al, ; Lutchmiah, Verliefde, Roest, Rietveld, & Cornelissen, ; Yip, Tiraferri, Phillip, Schiffman, & Elimelech, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] achieved an average water flux rate of 6 L·m -2 ·h -1 with diluted wastewater and used 0.5 M NaCl as the model draw solution when using a cellulose triacetate membrane (CTA) from HTI. Similar values were also obtained by Holloway et al [37], who reported water fluxes of 13 10.1 L·m -2 ·h -1 for concentrated anaerobic digests using CTA membranes from HTI.…”
Section: Water Fluxesmentioning
confidence: 99%
“…Wang et al [15] recently published a study using real diluted municipal wastewater with solute rejections of ammonium and total nitrogen (TNt) of 68% and 48%, respectively, and rejections of chemical oxygen demand (COD) and total phosphorus (TPt) of more than 99%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations